Dynamic fuzzy model for detecting verbal violence in real time - Campos, Obed; Pancardo, Pablo; Hernández-Nolasco, José Adán (Wydawnictwa AGH, 2022)
The crime rates in Mexico have been increasing in recent years, every day, there are reports on social media and in the news where assaults and verbal aggression by criminals can be seen. Public transportation units suffer from violence that authorities have not been able to reduce despite their efforts. This is why we have developed a fuzzy logic model that can adapt to almost any scenario thanks to the dynamism that we have implemented in each of its stages. We have obtained promising results that we believe will be of great help to the authorities for detecting the exact moment in which verbal aggression that is typical of a violent assault is happening in real time. This is a tool to help the authorities, not a substitution, we are simply making use of the latest technologies that are available to us. The goal of this paper is to provide a novel method for Mexican authorities in Mexico City in order to help the actual surveillance systems make faster decisions about whether violent assaults are happening or not.
Computer Science
Bibliogr. s. 490-493.
Keywords: fuzzy logic; dynamic; verbal violence; real time